Cycling with an amputation: A systematic review - Dyer, B. (Prosthetics and Orthotics International, 2015)
Background: Cycling with any form of limb amputation has progressed from an activity of leisure or rehabilitation to elite level competition as part of the Paralympic Games programme. Objective: While it is often proposed that research into sport with an amputation can be extremely limited, this study intended to identify the volume, type and historical strategy in this area. Study design: This study comprises a documented systematic literature review of cycling undertaken with any form of limb amputation. Method: This study used four online search engines to identify relevant peer-reviewed literature. These included SPORTDiscus, CINAHL, Scopus and MEDLINE. Google Scholar was also used as a secondary source. The initial results were then subjected to a set of pre-defined inclusion criteria. The resulting publications were then analysed for content and thematic commonality. Results: The review identified 20 articles which met pre-defined inclusion criteria. The identified peer-reviewed publications were dated from the period 2004 to 2014. Conclusions: Three clear themes emerged from the historical research. There was both a paucity of peer-reviewed literature with respect to cycling with an amputation and the design of adaptive or assistive technology to replace limb loss. However, publications have been rising substantially over the last 5 years. Clinical relevance: This review study established the historical strategy and content of cycling with an amputation and identified the existing research themes. This will assist in summarising the current level of knowledge and help signpost such work in the future.